Three new species of Caridina (Decapoda: Atyidae) from Central Sulawesi and Buton Island, Indonesia, and a checklist of the islands’ endemic species - Klotz, Werner; Rintelen, Kristina Von (Zootaxa, 2013)
Three atyid shrimp species of the genus Caridina Milne Edwards, 1837, Caridina boehmei n. sp., C. laroeha and C. bu-tonensis n. sp., are described from the Indonesian islands Sulawesi and Buton. Caridina boehmei n. sp. differs from its apparently next congener C. sulawesi Cai & Ng, 2009 by the shape of the spinulation of the male sexual appendages. Caridina laroeha resembles C. mahalona and C. opaensis, but can be distinguished by the length and armature of the ros-trum, the length ratio of segments of the third maxilliped and the number of spinules on the uropodal diaeresis. Caridina butonensis n. sp. resembles to C. boehmei n. sp. and C. opaensis but can be distinguished by its peculiar truncated rostrum and by a more reduced podobranch on the second maxilliped.